Pesticides as a risk factor for cognitive impairment: Natural substances are expected to become alternative measures to prevent and improve cognitive impairment - Wen, Liankui; Miao, Xiwen; Ding, Jia; Tong, Xuewen; Wu, Yuzhu; He, Yang; Zheng, Fei (Frontiers in Nutrition, 2023)
Pesticides are the most effective way to control diseases, insects, weeds and fungus. The central nervous system (CNS) is damaged by pesticides residues in various ways. Through consulting relevant databases, the systemic relationships between the possible mechanisms of pesticides damage to the CNS causing cognitive impairment and related learning and memory pathways networks, as well as the structure-activity relationships between some natural substances (such as polyphenols and vitamins) and the improvement were summarized in this paper. The mechanisms of cognitive impairment caused by pesticides are closely related. For example, oxidative stress, mitochondrial dysfunction and neuroinflammation can constitute three feedback loops that interact and restrict each other. The mechanisms of neurotransmitter abnormalities and intestinal dysfunction also play an important role. The connection between pathways is complex. NMDAR, PI3K/Akt, MAPK, Keap1/Nrf2/ARE, and NF-κB pathways can be connected into a pathway network by such targets as Ras, Akt, IKK, etc. The reasons for the improvement of natural substances are related to their specific structure, such as polyphenols with different hydroxyl groups. This review purpose is to lay a foundation for exploring and developing more natural substances which can effectively improve the cognitive impairment caused by pesticides.